Filling the institutional void: The social behavior and performance of family vs non-family technology firms in emerging markets - Miller, Danny; Lee, Jangwoo; Chang, Sooduck; Le Breton-Miller, Isabelle (Journal of International Business Studies, 2009)
Family businesses (FBs) are said to treat their employees with unusual consideration to form a cohesive internal “community”. They are also claimed to develop deeper, more extensive “connections” or relationships with outside stakeholders. Both behaviors may increase the viability of a business intended to support an owning family and its later generations. Such social linkages, we believe, may compensate for the lack of capital, product and labor institutional infrastructures in dynamic emerging economies. This survey study of a most challenging emerging-market sector, namely Korean high-technology businesses, argues three major points. (1) Relationships of community and connection will be more common in FBs than in non-FBs. (2) These relationships will enhance performance in emerging-market high-technology sectors, which, because of their competitive, complex, and ever-changing nature, rely on significant expert knowledge and social capital within and outside the organizational community. (3) The performance of FBs will benefit more from these community and connection relationships than the performance of non-FBs, because in these personally intimate settings employees and external partners will be especially likely to return the generosity of a visibly active owning family, or to penalize its selfishness. Significant empirical support was found for most of these hypotheses.